Some Bioethical Aspects Concerning Robotic Surgery in Brazil - de Magalhães, João Luiz (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2015)
Robotics is a technological development that brings benefits to surgical practice. However, it also brings dilemmas and ethical conflicts to the medical field. This work aims to discuss the ethics of the use of robots in surgeries in Brazil, based on the ethical and bioethical principles of equality, inequality and justice. I conclude that the philosophical reflection and the bioethical principles contribute to a consensus of the medical practices that aim health promotion and that not all inequalities are inequities. Thus, society should make interventions for the application of different approaches that compensate for unfair differences.